Toward a Typology of Child Sex Traffickers: Using Crime Script Analysis to Inform Prevention - Reid, Joan (Victims & offenders, 2023)
Preventing child sex trafficking remains an urgent concern for public health and criminal justice professionals. Using crime script analysis, this study identified a typology of child sex traffickers (CSTs). Data for this study were drawn from 78 child sex trafficking cases involving 54 CSTs and 48 victims of commercial sexual exploitation of children (CSEC) investigated by the Child Protective Investigation Unit in a predominately rural and suburban county. Using a decision tree model, we identified subtypes of child sex traffickers (CSTs) and explored patterns and variation in the victim recruitment tactics used by these subtypes during three phases of the victim recruitment crime script – find, groom, and exploit. Seven types of CSTs emerged from the cases: Peer/Acquaintance, Organized Crime, Family Abuser, Romantic Coercive Conman, “Mate Crime” Predator, Opportunistic, and Cyber traffickers. Both shared and unique tactics were identified such as social media and peer recruitment to find victims, promises, and gifts to groom victims, and threats and violence to ensnare victims. Based upon the study findings, we recommend specific prevention strategies and education themes related to the various at-risk situational scenarios and documented tactics used by CSTs at each phase of victim recruitment.